PENGARUH TARIF DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNAAN LAYANAN GO-RIDE (Studi Kasus Pada Pengguna Go-Ride di Kota Tangerang Selatan) - Rina Suci Wulandari; Apriatni Endang Prihatini (Universitas Diponegoro, 2018)
In globalization era as now, market competition getting strict especially in public transportation sector make Go-Ride have to establish strategy to compete the competitors. The problem in this research is decreased transaction and the transaction never achieve the target on Go-Ride service in 2015-2016 period. The purpose of this research is to determine the effect of price and service quality on the purchasing decision of Go-Ride service in South Tangerang City. The kind of this research is explanatory research, with the population of this researh is the user of GoRide service in South Tangerang City. While the sample is 100 respondents and the technique of sample using purposive sampling by using approach of sampling area. The analytical method using validity test, reliability test, correlation coefficient, coefficient of determination, simple linear regression analysis, multiple linear regression analysis, and significance test (t test and f test) using SPSS for Windows version 20.0. The price variables included into good category. The value of t count (1.859) > t table (1.660). Coefficient correlation 0,185 and coefficient determination 3,4%. Service quality variables included into good category. The value of t count (7,191) > t table (1.660). Coefficient of correlation 0,588 and coefficient of determination 34,5%. The purchasing decision variables included into good category. The value of f count (25,993) > f table (3.09). This research concludes that price and service quality have positive and significant effect to purchase decision. The results of this research indicate that although the variable of price and variable of service quality are good, but there are other factors that affect the purchase decision of Go-Ride service in South Tangerang City, that is consumers do not make Go-Ride service as the main priority in using online ojek transportation. Researchers advise companies to add Go-Ride advantages, for example by adding some new features in Go-Jek application such as telephone feature so consumer privacy is more secure, select drivers fiture, and change destination location fiture. Go-Ride also needs to add facilities that can increase consumer comfort while driving with Go-Ride.